Dasar Konstitusional Penetapan Peraturan Pemerintah Pengganti Undang-Undang dan Batasan Pengaturannya - Chrisdianto Eko Purnomo (Jatiswara, 2015)
The provisions of Article 22 paragraph (1) of the 1945 Constitution is the cornerstone of the constitutional President in determining Government Regulation in Lieu of Law (decree). However, in practice, the right of the President establishes decree can not be measured objectively about matters of urgency requirement that force. Whereas decree degree and have the same legal force with the Act. It is therefore necessary limits of determination decree by the President in order to avoid abuse of power. It is important, from the point of a government based on the Constitution (constitutionalism), with a tap on the point of fixing restriction decree pursuant to Article 22 paragraph (1) of the 1945 Constitution which should only regulate in the public administration (administratiefrechtelijk). Moreover, the restrictions implemented by applying the mechanism of checks and balances between the organs of state institutions, namely strengthening the supervisory function of the House of Representatives of the establishment decree by the President in accordance with Article 22 paragraph (2) and (3) of the 1945 Constitution.